Evaluation of an Intelligent Learning Environment for Young Children with Autism Spectrum Disorder - Zheng, Zhi (J Autism Dev Disord, 2016)
Researchers are increasingly attempting to develop and apply innovative technological platforms for early detection and intervention of Autism Spectrum Disorder (ASD). This pilot study designed and evaluated a novel technologically-mediated intelligent learning environment with relevance to early social orienting skills. The environment was endowed with the capacity to administer social orienting cues and adaptively respond to autonomous real-time measurement of performance (i.e., non-contact gaze measurement). We evaluated the system with both toddlers with ASD (n=8) as well as typically developing infants (n=8). Children in both groups were able to ultimately respond accurately to social prompts delivered by the technological system. Results also indicated that the system was capable of attracting and pushing toward correct performance autonomously without user intervention.